Toptimiz3D: A topology optimization software using unstructured meshes. (October 2020) - Aranda, Ernesto; Bellido, José Carlos; Donoso, Alberto
Highlights: In this paper we present Toptimiz3D, a topology optimization software with a graphical user interface for setting up and solving structural topology optimization problems. It can handle with general geometries and unstructured meshes in both 2d and 3d. Toptimiz3D permits the use of several optimization algorithms (MMA, IPOPT, optimality conditions) and numerical smoothing and projection techniques. The software allows the user to define a mesh and set up the problem selecting different options to solve it directly through the interface. Abstract: Toptimiz3D is a graphical user interface for setting up and solving structural topology optimization problems which can handle with general geometries and unstructured meshes. And it is precisely here where the emphasis is placed on. Unlike other existing educational softwares, Toptimiz3D is intended to go a bit further as the aforementioned strengths allow us to face more realistic situations and therefore optimize structures coming for real-world problems. It solves five types of topology optimization benchmark problems (single and multiple loads compliance problem, the volume problem, compliant mechanism design and the stress constrained problem) by means of the SIMP method. Moreover, three optimization algorithms are included (MMA, IPOPT, OC), and two types of filters are incorporated (density filter with a conic function and a Helmholtz-type PDE-based filter). This application offers a user-friendly environment to specify all relevant data in order to define a topology optimization problem and solve it directly from the interface. Toptimiz3D is a free-distribution software open to future development.